Edward Y. ODISHO. Pronunciation is in the Brain, not in the Mouth. A Cognitive Approach to Teaching it. Piscataway, NJ: Gorgias Press LLC, 2014, xxv + 248 pp. ISBN 978-1-4632-0415-0 - Pinto, Maria da Graça L. Castro (Linguarum Arena, 2015)
.